The Criteria for Evaluation of the Integration of Information and Communication Technology in the Curriculum - Abbas Hossiny (Journal of Medical Education Development, 2020)
Objective: This study aimed to review the criteria for evaluating the integration of information and communication technology (ICT) in the curriculum, and given its significance, provide the necessary assessment recommendations. Material & Methods: This study was a theoretical-systematic review performed with keywords such as "integration," "evaluation," "Information and communication technology," "medical education," and "curriculum" in the Latin databases of Ovid Science direct and PubMed. Similar Farsi keywords were looked up in SID, Iranmedex, Normagez, and Magiran databases by the search engines of Google and Yahoo from 2008 to 2019. From a total number of 158 articles, 22 works were selected according to the inclusion criteria such as the study title, objectives, and specified timeframe, and were analyzed by the synthesis research method. Results: According to the results, criteria such as support, educational materials and resources, teacher, student, and assessment were influential in evaluating the integration of ICT in the curriculum. The evaluating criteria of this study were extracted as following, teacher (knowledge, ICT skills), student (interaction, skills of digital content creation), support (planning, culture, and human resources training), educational materials and resources (hardware and software resources, digital content), and educational assessment (feedback, digital assessment and cartable). Conclusion: According to the results of the study, the criteria for evaluating the integration of ICT can be a valuable framework for higher education experts and officials to provide critical curriculum improvements, enhance the quality of assessment, and facilitate the educational procedure.